ANALISIS POTENSI DAN STRATEGI PENGEMBANGAN OBJEK WISATA PULAU ASEY BESAR DANAU SENTANI KABUPATEN JAYAPURA - Ilham Ilham; Ferry Yan Korwa; Usman Idris; M Zaenul Muttaqin (Universitas Merdeka Malang, 2020)
A particular charm accompanies the existence of several islands in the Lake Sentani area. An example of such places is Asey Besar Island, which is frequently visited by tourists and has several natural spots and historical heritage assets. Consequently, this research was conducted to map the potential tourist spots that have become attractions in Asey Besar Island. It was also performed to reveal the environmental conditions by utilizing Sapta Pesona or the seven enchantments’ elements. A qualitative descriptive approach was used for the research, while a SWOT analysis was performed to formulate alternative strategies that are potentially useful in developing tourism in the area. The study results showed that the Sapta Pesona concept had not been fully realized and revealed potential tourist spots and attractions for the island. These spots include a white ship, an old church, bark carvings, water, and cultural tourism, as well as the Lake Sentani Festival. Alternative strategies that were found useful in developing Asey Besar Island tourism objects are the provision of road infrastructure and building tourism support facilities, such as cafes, homestays, and Instagramable photo spots. Other strategies are improving the environmental quality, maintaining cleanliness, performing effective tourism promotion activities, as well as supporting and realizing the development of tourism objects based on Sapta Pesona.